KEJAHATAN KORUPSI BIDANG PERTANIAN : PELANGGARAN HAK ASASI MASYARAKAT DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT YANG BERKEADILAN SOSIAL - Sri Lestariningsih (Fakultas Hukum Universitas Riau, 2013)
Food is a major necessity forhuman life in the world, evenfrom a very close association withfood clashing civilizations. But thefacts show that tngkat corruptionin ministries / agencies in the fieldof agriculture in central Indonesiawas ranked first based on datacorruption by authority. Based onthe specificity of the nature of thecrimeofcorruption,theenforcement of this crime requiresspecific ways as well. Lawenforcementforcrimesofcorruption needs to be donesimultaneouslyandsynergy,between the law enforcementdilaterapkankonsitenwithgovernment strategic policies inagriculture or food, so the risk orimpact of corruption crimes thatoccurred in the field of food willnot be just too bad for society.